Navy bean cotyledon cells : isolation, characterisation and their application in low glycaemic bread : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Palmerston North, Manawatū, New Zealand - Yu, Wenwen (Massey University, 2022)
There is an increasing consumer demand for low-glycaemic foods due to the rise in lifestyle diseases such as obesity and type 2 diabetes globally. Reducing the glycaemic response of starch-based foods is a challenge as it leads to a significant change in their texture. Pulses are one of the most popular foods and known to have a low glycaemic index (GI). Recently it has been suggested that their isolated cotyledon cells can play an important role in delaying the digestion rate of starch, due to their unique structure where starch granules are tightly embedded in a protein matrix surrounded by the intact cell walls. Studies have been reported on the lab-scale isolation of gelatinised as well as ungelatinised cotyledon cells from navy beans, but rarely investigated the mechanisms by which their cell structure (cell walls, intracellular proteins) controls the starch digestibility. In the present study, intact cotyledon cells from navy beans were extracted using different processing conditions including acid–alkali treatments, autoclaving and hydrothermal processing, and their properties were compared to their counterpart navy bean starch to understand changes in the starch structure and in vitro digestibility. Furthermore, the effect of partial substitution of wheat flour with isolated cells on physicochemical and textural properties, starch hydrolysis kinetics and digesta characteristics during oral, gastro-small intestinal digestion in vitro was studied. Light micrographs and SEM images of the isolated cells through acid–alkaline treatment showed the presence of intact cells containing ungelatinised starch granules embedded in the protein matrix. The in vitro starch digestion curves showed that cells with different treatments display different cell permeability and different digestion kinetics, thus affecting the starch digestibility. Regarding bread with cotyledon cells, adding 25% and 50% cotyledon cells to bread decreased the specific volume and whiteness of bread and increased breadcrumb and crust hardness. SEM observation evidenced that the integrity of the cell wall in bread was preserved in baked bread as well as digesta, and this led to a ~34% reduction in vitro digestibility compared to white bread when 50% of the wheat flour was replaced with intact cells. Selected samples of the bread were evaluated for their glycaemic indices through in vivo (human) trials. A similar in vitro digestion-like trend was observed during in vivo (human) digestion studies. The results of the study suggested that bread with 50% of wheat flour replaced by cotyledon cells may be considered as low GI bread. This study is expected to propose an optimized process suitable for commercial production of cotyledon cells from pulses and their application to develop low GI baked products such as bread.
All Figures in Chapter Two are re-used with the publishers' permission.
Keywords: cotyledon cell; starch digestibility; glycaemic response; bread; 400405 Food engineering